Answer :

Let f(x) =

By product rule

=(x2 + 1)(-sinx) + cosx × 2x

= -x2sinx - sinx+2x cosx

f’(x) = - x2 sin x – sin x + 2x cos x

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

<span lang="EN-USMathematics - Exemplar

<span lang="EN-USMathematics - Exemplar